Aplikasi Model Konseptual Keperawatan Pamela G Reed “Self-Transcendence” pada Kasus Kanker Payudara - Nurhayati, Nurhayati; Nursanti, Irna (Jurnal Sains, Teknologi dan Kesehatan, 2024)
Pamela G. Reed publishes a theory of self-transcendence, which states that the development of self-concept is limited multidimensionally, namely inwardly, outwardly and temporally (worldly). Nursing actions directly focus on sources that originate from within a person towards transcendence or focus on several personal and contextual factors that influence the relationship between self-transcendence and vulnerability, the relationship between self-transcendence and good/healthy conditions. This paper analyse the application of Reed’s theory on a breast cancer patient.